2004
DOI: 10.1128/jvi.78.13.7227-7247.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transduction and Cell Entry Pathway of Fiber-Modified Adenovirus Type 5 Vectors Carrying Novel Endocytic Peptide Ligands Selected on Human Tracheal Glandular Cells

Abstract: Monolayers of cystic fibrosis transmembrane conductance regulator (CFTR)-deficient human tracheal glandular cells (CF-KM4) were subjected to phage biopanning, and cell-internalized phages were isolated and sequenced, in order to identify CF-KM4-specific peptide ligands that would confer upon adenovirus type 5 (Ad5) vector a novel cell target specificity and/or higher efficiency of gene delivery into airway cells of patients with cystic fibrosis (CF). Three different ligands, corresponding to prototypes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…47 In addition to cellular binding, the fiber and its knob domain have been suggested to carry several functions important for intracellular trafficking, membrane lysis and virus maturation. [20][21][22][23][24][25] Fiber content of FibDCAR-HI-Link-ZHZH viruses was 12-29% of WT, which is an improvement from earlier studies where knobless virions have had fiber content of 2-10%. 10 Another improvement of Ad5/FibDCAR-HI-Link-ZHZH was the PP-to-PFU ratio, which was 140, as compared to 70 for the WT virus.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…47 In addition to cellular binding, the fiber and its knob domain have been suggested to carry several functions important for intracellular trafficking, membrane lysis and virus maturation. [20][21][22][23][24][25] Fiber content of FibDCAR-HI-Link-ZHZH viruses was 12-29% of WT, which is an improvement from earlier studies where knobless virions have had fiber content of 2-10%. 10 Another improvement of Ad5/FibDCAR-HI-Link-ZHZH was the PP-to-PFU ratio, which was 140, as compared to 70 for the WT virus.…”
Section: Discussionmentioning
confidence: 79%
“…12,40 These growth defects can be explained by a low-fiber content caused by the lack of the fiber knob hampering virus entry and intracellular trafficking and a loss of other growth -or viral assembly functions carried by the fiber knob. [20][21][22][23][24][25] Only in the de-knobbed virus Ad5/R7-C2C2, containing the Ig binding C2 domain from Streptococcal protein G, we found a normal fiber content indicating that this fiber somehow compensates, as far as fiber content of the virus is concerned, for the loss of the fiber knob. 40 Therefore, a novel approach was also employed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar 'de-knobbing' strategy was employed by Magnussen et al, 111 wherein an integrin-binding RGD motif was utilized, resulting in selective infection of integrin-expressing cell lines in vitro, as well as human glandular cells. 112 Based on the feasibility of fiber replacement with T4 fibritin, an elegant system was devised wherein the trimeric CD40 ligand was fused to the C-terminus of this artificial fiber. 113 Notably, this vector provided CD40-specific gene delivery in vivo following systemic delivery.…”
Section: Adenovirus Targeting Via Genetic Modification: Fibermentioning
confidence: 99%
“…The efficiency of Ad vectors in gene transfer has been demonstrated in numerous systems (Henning et al, 2002;Gaden et al, 2004;Toh et al, 2005) and the functional analysis of transgenes expressed by Ad can be tested in vitro in cell lines, ex vivo in tissues and in vivo in animal models. In vitro studies demonstrated that recombinant Ad vectors can express CFTR in cultured CF airway epithelial cells and correct the Cl -transport defect (Zabner et al, 1993).…”
Section: Adenovirus (Ad) Vectormentioning
confidence: 99%